Determinan Sosial-Ekonomi terhadap Kemiskinan di Provinsi Nusa Tenggara Timur dengan Pendekatan Regresi Data Panel Tahun 2017-2023 - Farisa Farisa; Firda Dessya Dwitanti; Muhammad Zacky Arie Pratama; Risma Alifiyanti; Febri Wicaksono (Jurnal Ekonomi-Qu, 2025)
Poverty remains one of the structural problems still faced by Indonesia, particularly in East Nusa Tenggara Province (NTT), where the poverty rate consistently exceeds the national average. This study aims to analyze the influence of socioeconomic factors on poverty levels in NTT during the 2017–2023 period. This study employs Gross Regional Domestic Product (GRDP), Human Development Index (HDI), and Open Unemployment Rate (OUR) as the independent variables, while the dependent variable is the proportion of the population living in poverty. The method employed is panel data regression using fixed effect and random effect models, selected based on the results of the Chow test, Hausman test, and Lagrange Multiplier test to obtain the best estimation model. The findings show that HDI and GRDP per capita have a negative and significant effect on poverty levels, while the Open Unemployment Rate has a positive but not statistically significant effect. These findings highlight the importance of improving human capital and promoting inclusive job creation in poverty reduction efforts in NTT. This study is expected to provide empirical contributions for local governments in formulating more effective, contextual, and data-driven socioeconomic development policies.